Estimation of Groundwater Recharge from Rainfall for Arid Coastal Plain of Ninh Thuan Province, Vietnam - Nguyen Van Hoang; Trinh Thu; Shakirov Renat; Tran Thi Thuy Huong; Syrbu Nadezhda (Russian Journal of Earth Sciences, 2022)
Estimation of groundwater recharge from rainfall is a key factor for determining groundwater resources in water development and management for supporting sustainable socio-economic development, especially for arid areas. The paper presents finite element modeling in the simulation of moisture transfer in unsaturated soils through the relationship between soil moisture, soil suction, unsaturated permeability and soil-moisture dispersivity. Those parameters required for soil moisture transfer are derived from the soil-water characteristic curve functions. Element sizes and time steps used in the modelling have been selected based on a detailed analysis of numerical simulation errors. The methodology had been applied to arid coastal plain area of Ninh Thuan province, Vietnam. Five subsurface soil types in the study area have been collected and analyzed, for saturated permeability, porosity, saturated soil water content, field moisture content, etc. Hourly rainfall data of the years 2014–2018 have been analyzed and grouped into different-duration rainfall events (1-hour, 2-hour, 3-hour and so on). The different rainfall durations and depths of rainfall events and temporal infiltration determined by the moisture transfer modelling have allowed determining the groundwater recharge from the rainfall data. The results show that during the rainy months from May to December 2014–2018, the groundwater recharge from the rainfall is very varying through the modeled soil profiles, from 0.280 m (silty clay) to 0.470 m (sandy silt), which is equivalent to 33.3%–55.2% of the rainfall depth during May–December. Lower infiltration in silty clay is due to low permeability and in the sand is due to low suction, and higher infiltration in silt and sandy silt is thanks to their higher moisture dispersivity. On average, in terms of annual rainfall and soil properties, the average infiltration during May–December is 0.380 m which is equivalent to 44.9% of the rainfall depth, which is about 289 x 106 m3 of rainwater infiltrated into the Quaternary aquifer over 760 km2 of the coastal plain of Ninh Thuan province. The results would be very useful for effective water resources development and management in a given specific hydrogeological condition for such a severe drought area where water is extremely essential.